Evaluación de sistemas de producción de grano con distinta intensidad en el uso de insumos - Andersen, Martin; Cicchino, Mariano Andres; Bailleres, Matias Andres; Garello, Federico José; Rolon, Juan (Ministerio de Desarrollo Agrario de la Provincia de Buenos Aires, 2024)
Póster